Optimasi Kinerja Algoritma AES-128 Pada Proses Enkripsi dan Dekripsi File Berbasis Python - Wulandari, Siti; Indra, Zulfahmi; Ridho, Muhammad (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
Data security is a top priority in the digital era, especially in the face of increasing cyber threats. Advanced Encryption Standard (AES) is one of the most widely used cryptographic algorithms to protect data. The purpose of this study is to implement the AES algorithm in the Python programming language using the Google Colab platform to improve data security in an efficient manner. This implementation explores the use of AES to perform secure and fast data encryption and decryption, and evaluates the algorithm's performance in terms of speed and resource efficiency. The study shows that AES-128 is able to encrypt data in an average time of 0.003663 seconds and decrypt data in 0.000112 seconds. The file size increases by only 17% after encryption, indicating efficiency in resource usage. The Google Colab platform has been shown to improve computational performance, especially in the fast decryption process without compromising data security.Kata kunci: AES, Optimasi, Pyhton